2020
DOI: 10.1007/978-3-030-60425-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence and Machine Learning in Producing Actionable Cyber Threat Intelligence

Abstract: Cyber Threat Intelligence (CTI) can be used by organisations to assist their security teams in safeguarding their networks against cyber-attacks. This can be achieved by including threat data feeds into their networks or systems. However, despite being an effective Cyber Security (CS) tool, many organisations do not sufficiently utilise CTI. This is due to a number of reasons such as not fully understanding how to manage a daily flood of data filled with extraneous information across their security systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…It is often difficult to obtain consistent results and the required quality of the image with each test image due to several interferences and limitations of this technique. It is often observed that pre-defined algorithms or scripts may work fine for a certain set of images while it may not be able to process other sets of images due to inconsistencies that may be due to various factors [82,83]. To address these issues, various AI and machine learning tools can be adopted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is often difficult to obtain consistent results and the required quality of the image with each test image due to several interferences and limitations of this technique. It is often observed that pre-defined algorithms or scripts may work fine for a certain set of images while it may not be able to process other sets of images due to inconsistencies that may be due to various factors [82,83]. To address these issues, various AI and machine learning tools can be adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning will enable the processing of large datasets, and train prediction models which can implement intelligence as per the training models. This would give higher accuracy of the obtained results [82][83][84]. As per the extensive review carried out for this study, numerous technologies are currently being used involving artificial intelligence and machine learning; however, not much work is being carried out to integrate technologies for enhanced management of floods.…”
Section: Rq-4 How Can the Authorities Improve The Existing Flood Management Operation With Cutting-edge Technologies?mentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the need for implementing a more effective and proactive security approach such as threat intelligence (TI) [13,14]. TI refers to any evidence or event-based knowledge about potential attacks that highlight the risk landscape [15]. It can be described as a big picture of the attacker's intention and capability to target a specific asset that enables the organization (e.g.…”
Section: Introductionmentioning
confidence: 99%